Glyphosate-induced lipid metabolism disorder contributes to hepatotoxicity in juvenile common carp. (15th January 2021) - Liu, Jingbo; Dong, Chenyu; Zhai, Zhenzhen; Tang, Liang; Wang, Lin
Abstract: Residues of glyphosate (GLY) are widely detected in aquatic systems, raising potential environmental threats and public health concerns, but the mechanism underlying GLY-induced hepatotoxicity in fish has not been fully elucidated yet. This study was designed to explore the hepatotoxic mechanism using juvenile common carp exposed to GLY for 45 d, and plasma and liver samples were collected at 15 d, 30 d, and 45 d to analyze the assays. First, GLY-induced hepatic damage was confirmed by serum liver damage biomarker and hepatic histopathological analysis. Next, changes in oxidative stress biomarkers, gene expression levels of pro- and anti-inflammatory cytokines, and lipid metabolism-related parameters in collected samples were analyzed to clarify their roles in GLY-induced hepatic damage. Data showed that oxidative stress was an early event during GLY exposure, followed by hepatic inflammatory response. Lipid metabolism disorder was a late event during GLY exposure, as evidenced by overproduced hepatic free fatty acids, enhanced lipogenesis-related gene expression levels, reduced lipolysis-related gene expression levels, and resultant hepatic lipid accumulation. Collectively, these findings demonstrate that GLY induces hepatotoxicity in fish through involvement of oxidative stress, inflammatory response, and lipid metabolism disorder, which are intimately interrelated with each other during GLY exposure. Graphical abstract: Image 1 Highlights: Sub-chronic glyphosate (GLY) exposure induces hepatic damage in fish. Oxidative stress and resultant inflammatory response are involved in GLY-exposed fish. GLY-induced inflammation contributes to hepatic lipid metabolism disorder in fish. GLY-induced hepatotoxicity in fish is due to lipid metabolic disorders.